The necessary and sufficient conditionfor iintegrability is
"R(\\frac{\\partial P}{\\partial y}-\\frac{\\partial Q}{\\partial x})+P(\\frac{\\partial Q}{\\partial z}-\\frac{\\partial R}{\\partial y})+Q(\\frac{\\partial R}{\\partial x}-\\frac{\\partial P}{\\partial z})=0"
"-(1+xy)(z-(z-2x))+(1+yz)(x+x)+x(z-x)(-y-y)="
"=-2x-2x^2y+2x+2xyz-2xyz+2x^2y=0"
Thus, the given equation is integrable.
"(1+yx)dz\u2212(1+yx)dx\u2212x(z\u2212x)dy\u2212y(z\u2212x)dx=0"
"(1+yx)d(z\u2212x)\u2212(xdy+ydx)(z\u2212x)=0"
"(1+yx)d(z\u2212x)\u2212d(1+xy)(z\u2212x)=0"
"\\frac{d(z-x)}{z-x}-\\frac{d(1+xy)}{1+xy}=0"
"ln(z\u2212x)\u2212ln(1+xy)=lnc_1\n\u200b"
"\\frac{z-x}{1+xy}=c_1"
Comments
Leave a comment